Making learning fun: Implementing interactive media in early childhood education - Qonita Chiara Darmawan; Khusnul Laely; Dewi Puspitasari; Safitri Safitri; Ervina Salsabila; Dhina Ayu Lestari; Yonanda Meisya Kesuma; Nani Kuswandani; Himatul Aliyah; Arifah Nur Hidayati; Tri Novita Siam Ningsih (Community Empowerment, 2024)
Common challenges in institutional learning include a lack of learning media for educators to deliver content effectively. This community service addresses this issue by providing learning resources such as busy book ‘Clean the Teeth’, creation blocks, interactive fruits quiz, and story book ‘Ablution and Tayamum’. The goal is to supplement educators' materials for teaching tooth brushing, healthy eating, ablution procedures, tayamum, and interactive games to children, thereby enhancing knowledge acquisition. This service involves implementing these media into the learning process. Results indicate increased student knowledge of tooth brushing, healthy foods, ablution, and tayamum procedures, as well as improved engagement with interactive media.